Witches of Brooklyn. 2, What the hex?! - Escabasse, Sophie (RH Graphic, 2021)
Effie is officially introduced to the other witches of Brooklyn. When she she returns to school, Berrit has made a new friend and Effie feels like she's ignoring her. But when Effie learns the new girl has magic in her too, Selimene and Carlota offer to help train her as a witch as well.